Growth and optical investigations of high quality individual CdTe/(Cd, Mg)Te core/shell nanowires. (21st December 2016) - Wojnar, P; Płachta, J; Kret, S; Kaleta, A; Zaleszczyk, W; Szymura, M; Wiater, M; Baczewski, L T; Pietruczik, A; Karczewski, G; Wojtowicz, T; Kossut, J
Abstract: CdTe nanowires with the average diameter of only 40 nm coated with (Cd, Mg)Te shells are grown using Au-catalyzed vapor–liquid–solid growth mechanism in a system for molecular beam epitaxy. High optical quality of individual nanowires is revealed by means of low temperature cathodoluminescence and micro-luminescence. It is found that, the optical emission spectrum consists mostly of the near band edge emission without any significant contribution of defect related luminescence. Moreover, the importance of surface passivation with (Cd, Mg)Te coating shells is demonstrated.